Hepatotoxic mechanism of cantharidin: insights and strategies for therapeutic intervention - Jin, Dian; Huang, Na-Na; Wei, Jing-Xia (Frontiers in Pharmacology, 2023)
Cantharidin (CTD), a natural compound derived from Mylabris, is widely used in traditional Oriental medicine for its potent anticancer properties. However, its clinical application is restricted due to its high toxicity, particularly towards the liver. This review provides a concise understanding of the hepatotoxic mechanisms of CTD and highlights novel therapeutic strategies to mitigate its toxicity while enhancing its anticancer efficacy. We systematically explore the molecular mechanisms underlying CTD-induced hepatotoxicity, focusing on the involvement of apoptotic and autophagic processes in hepatocyte injury. We further discuss the endogenous and exogenous pathways implicated in CTD-induced liver damage and potential therapeutic targets. This review also summarizes the structural modifications of CTD derivatives and their impact on anticancer activity. Additionally, we delve into the advancements in nanoparticle-based drug delivery systems that hold promise in overcoming the limitations of CTD derivatives. By offering valuable insights into the hepatotoxic mechanisms of CTD and outlining potential avenues for future research, this review contributes to the ongoing efforts to develop safer and more effective CTD-based therapies.